2019
DOI: 10.1021/acs.est.9b02639
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Improves Performance of Anaerobic Membrane Bioreactor Treatment of Food Waste at High Organic Loading Rates

Abstract: Anaerobic membrane bioreactors (AnMBRs) are in use at the full-scale for energy recovery from food waste (FW). In this study, the potential for two-phase (acid/gas) AnMBR treatment of FW was investigated as a strategy to increase microbial diversity, thereby improving performance. Two bench-scale AnMBRs were operated in single-phase (SP) and two-phase (TP) mode across incremental increases in organic loading rate (OLR) from 2.5 to 15 g total chemical oxygen demand (COD) L•d −1 . The TP acid-phase (TP-AP) enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…Amha, Corbett, and Smith (2019) investigated bench‐scale AnMBR treatment of Food Waste both for Single‐Phase and Two‐Phase (acid‐phase and methane‐ phase) by looking at biogas production and microbiological community dynamics of these systems at various Organic Loading Rates up to 15 g COD L/day. The two‐phased mode was found more effective in treating food waste at low pH.…”
Section: Fixed Film and Anaerobic Mbrmentioning
confidence: 99%
“…Amha, Corbett, and Smith (2019) investigated bench‐scale AnMBR treatment of Food Waste both for Single‐Phase and Two‐Phase (acid‐phase and methane‐ phase) by looking at biogas production and microbiological community dynamics of these systems at various Organic Loading Rates up to 15 g COD L/day. The two‐phased mode was found more effective in treating food waste at low pH.…”
Section: Fixed Film and Anaerobic Mbrmentioning
confidence: 99%
“…The potential of a two-phase (acid phase followed by gas phase) anaerobic membrane bioreactor (AnMBR) to treat food waste by attempting to increase the microbial diversity and improve performance was evaluated by Amha, Corbett, and Smith (2019). The authors found that the two-phase AnMBR treatment improved the rate of hydrolysis, increased the diversity of the microbial consortium, and enhanced syntrophic activity in the system.…”
Section: Annual Literature Reviewmentioning
confidence: 99%
“…Anaerobic membrane bioreactors (AnMBRs), which combine anaerobic digestion and membrane separation to improve effluent quality and increase biogas production, are an attractive biotechnology for organic waste management (Smith et al, 2012;. Amha et al (2019) demonstrated that AnMBR management of food waste (FW) provided >95% chemical oxygen demand (COD) removal. Further, AnMBR was reported to produce 0.13-0.18 L CH 4 per g of COD removed during treatment of food processing wastewater with a net energy benefit of 0.16-1.82 kWh m −3 (Galib et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study on FW management in TP AnMBRs demonstrated a significant increase in methane production compared to SP AnMBRs at ORLs up to 10 gCOD L −1 d −1 . The increase, ranging from 15.2 to 20.3%, was a result of increased VFA production (up to three times compared to the influent FW) in the AP of the TP reactor and increased diversity of the microbial community with higher activity of syntrophic fatty acid oxidizers in the TP-MP reactor compared to the SP reactor (Amha et al, 2019). However, the economic feasibility of a TP over a SP AnMBR is yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%